Cars, compounds and containers: Judicial and extrajudicial infrastructures of punishment in the ‘old’ and ‘new’ South Africa - Super, Gail (Punishment & society, 2022)
This paper examines non-state infrastructures of vigilante violence in marginalized spaces in South Africa. I argue that car trunks, shacks, containers, and other everyday receptacles function as the underside of official institutions, such as prisons and police lock-ups, and bear historical imprints of the extrajudicial punishments inflicted on black bodies during colonialism and apartheid. I focus on two techniques: forcing someone into the trunk of a vehicle and driving them around to locate stolen property, and confinement in garages, shacks, containers, or local public spaces. Whereas in formerly ‘whites only’ areas, residents have access to insurance, guards, gated communities, fortified fences, and well-resourced neighbourhood watches, in former black townships and informal settlements, this is not the case. Here, the boot, the shack, the shed, the car, and the minibus taxi play multiple roles, including as vectors and spaces of confinement, torture, and execution. Thus, spatiotemporality affects both how penal forms permeate space and time, and how space and time constitute penal forms. These vigilante kidnappings and forcible confinements are not mere instances of gratuitous violence. Instead, they mimic, distort, and amplify the violence that underpins the state's unrealized monopoly over the violence inherent in its claims to police and punish.